2022
DOI: 10.1002/nbm.4775
|View full text |Cite
|
Sign up to set email alerts
|

Motion correction for native myocardial T1 mapping using self‐supervised deep learning registration with contrast separation

Abstract: In myocardial T 1 mapping, undesirable motion poses significant challenges because uncorrected motion can affect T 1 estimation accuracy and cause incorrect diagnosis.In this study, we propose and evaluate a motion correction method for myocardial T 1 mapping using self-supervised deep learning based registration with contrast separation (SDRAP). A sparse coding based method was first proposed to separate the contrast component from T 1 -weighted (T1w) images. Then, a self-supervised deep neural network with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…For comprehensive CMR myocardium tissue examination in clinical practice, generally including pre−/post‐contrast T 1 and T 2 mapping, although a dedicated deep‐learning fitting model could be built for each T 1 or T 2 mapping sequence, the proposed DeepFittingNet in the multi‐tasking manner could further simplify the post‐processing because there is no need to prepare models for different tasks (e.g., inversion‐recovery T 1 mapping and T 2 ‐prep bSSFP) or select models for specific applications (e.g., MOLLI5(3)3 for pre‐contrast T 1 and MOLLI4(1)3(1)2 for post‐contrast T 1 ). In the future, Pixel‐wise DeepFittingNet could be integrated into the workflow of reconstruction, quality control, motion correction, and segmentation, to further simplify and achieve fully automatic processing for myocardium tissue characterization 31‐33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For comprehensive CMR myocardium tissue examination in clinical practice, generally including pre−/post‐contrast T 1 and T 2 mapping, although a dedicated deep‐learning fitting model could be built for each T 1 or T 2 mapping sequence, the proposed DeepFittingNet in the multi‐tasking manner could further simplify the post‐processing because there is no need to prepare models for different tasks (e.g., inversion‐recovery T 1 mapping and T 2 ‐prep bSSFP) or select models for specific applications (e.g., MOLLI5(3)3 for pre‐contrast T 1 and MOLLI4(1)3(1)2 for post‐contrast T 1 ). In the future, Pixel‐wise DeepFittingNet could be integrated into the workflow of reconstruction, quality control, motion correction, and segmentation, to further simplify and achieve fully automatic processing for myocardium tissue characterization 31‐33 …”
Section: Discussionmentioning
confidence: 99%
“…In the future, Pixel-wise DeepFittingNet could be integrated into the workflow of reconstruction, quality control, motion correction, and segmentation, to further simplify and achieve fully automatic processing for myocardium tissue characterization. [31][32][33] Previous studies have shown that physics/model-driven unrolling iterative deep-learning method can improve performance and interpretability. 34 In this study, we repeated the last two layers of FCNN of DeepFittingNet and utilized the difference between the measured and synthesized signals to simulate the procedure of minimizing residual in the conventional fitting.…”
Section: Discussionmentioning
confidence: 99%
“…AI algorithms can also be used to reduce artefacts and to improve the accuracy of native myocardial value estimation. Li et al [ 87 ] evaluated a motion correction method for myocardial T1 mapping using self-supervised deep learning-based registration with contrast separation (SDRAP). Results showed that the AI algorithm achieved the highest DSC of 85.0 ± 3.9% and the lowest mean boundary error (MBE) of 0.92 ± 0.25 mm among the methods compared.…”
Section: Ai In Cardiac Magnetic Resonancementioning
confidence: 99%
“…Motion correction and mapping took about 30 s per 2D slice. Li and Wu et al also showed a self-supervised registration method with contrast separation to improve motion characterization in mapping ( 51 ). The proposed deep learning registration approach was implemented on a GPU and shortened the computation time from 3.7 to 0.5 s. Additionally, an experienced cardiologist evaluated image quality of maps and images, finding an increase in image quality and reduction in motion artifacts when compared to standard motion correction methods.…”
Section: D Mappingmentioning
confidence: 99%
“…Deep learning methods have also been explored for 2D T 1 mapping: Gonzales et al used T 1 w images to train a coarse-to- (51). The proposed deep learning registration approach was implemented on a GPU and shortened the computation time from 3.7 to 0.5 s. Additionally, an experienced cardiologist evaluated image quality of T 1 maps and T 1 w images, finding an increase in image quality and reduction in motion artifacts when compared to standard motion correction methods.…”
Section: Respiratory Motion Correction Within Breath-holdsmentioning
confidence: 99%